Effect of Different Inoculum Combination on Biohydrogen Production from Melon Fruit Waste - Amekan, Yumechris; Wangi, Dyah Sekar A P; Cahyanto, Muhammad Nur; Sarto, Sarto; Widada, Jaka (Center of Biomass & Renewable Energy, Diponegoro University, 2018)
The natural microbial consortium from many sources widely used for hydrogen production. Type of substrate and operating conditions applied on the biodigesters of the natural consortium used as inoculum impact the variation of species and number of microbes that induce biogas formation, so this study examined the effect of different inoculum source and its combination of biohydrogen production performance. The hydrogen producing bacteria from fruit waste digester (FW), cow dung digester (CD), and tofu waste digester (TW) enriched under strictly anaerobic conditions at 37OC. Inoculums from 3 different digesters (FW, CD, and TW) and its combination (FW-CD, CD-TW, FW-TW, and FW-CD-TW) were used to test the hydrogen production from melon waste with volatile solids (VS) concentration of 9.65 g/L, 37Â°C and initial pH 7.05 Â± 0.05. The results showed that individual and combined inoculum produced the gas comprising hydrogen and carbon dioxide without any detectable methane. The highest cumulative hydrogen production of 743 mL (yield 207.56 mL/gVS) and 1,132 mL (yield 231.02 mL/gVS) was shown by FW and FW-CD-TW, respectively. Butyric, acetate, formic and propionic were the primary soluble metabolites produced by all the cultures, and the result proves that higher production of propionic acid can decrease hydrogen yield. Clostridium perfringens and Clostridium baratii prominently seen in all single and combination inoculum. Experimental evidence suggests that the inoculum from different biodigesters able to adapt well to the environmental conditions and the new substrate after a combination process as a result of metabolic flexibility derived from the microbial diversity in the community to produce hydrogen. Therefore, inoculum combination could be used as a strategy to improve systems for on-farm energy recovery from animal and plant waste to processing of food and municipal waste.Article History: Received February 5th 2018; Received in revised form May 7th 2018; Accepted June 2nd 2018; Available onlineHow to Cite This Article: Amekan, Y., Wangi, D.S.A.P., Cahyanto, M.N., Sarto and Widada, J. (2018) Effect of Different Inoculum Combination on Biohydrogen Production from Melon Fruit Waste. Int. Journal of Renewable Energy Development, 7(2), 101-109.https://doi.org/10.14710/ijred.7.2.101-10